2022
DOI: 10.3346/jkms.2022.37.e99
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons Between Normocalcemic Primary Hyperparathyroidism and Typical Primary Hyperparathyroidism

Abstract: Background Normocalcemic primary hyperparathyroidism (NPHPT) was first described in 2008. It is defined as consistently elevated serum parathyroid hormone (PTH) levels with normal serum calcium (sCa) concentration, after excluding secondary causes of PTH elevation. However, the exact definition and management strategy for NPHPT remain controversial. We retrospectively investigated the clinicopathological features and short-term outcomes of NPHPT patients. Methods A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(49 reference statements)
0
3
1
Order By: Relevance
“…In our study, contrary to the study of Choi HR et al. ( 24 ) we found that patients with NPHPT had a lower prevalence of fractures compared to HPHPT although the bone densitometry scores and bone turnover markers were similar in both groups.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In our study, contrary to the study of Choi HR et al. ( 24 ) we found that patients with NPHPT had a lower prevalence of fractures compared to HPHPT although the bone densitometry scores and bone turnover markers were similar in both groups.…”
Section: Discussioncontrasting
confidence: 99%
“…The most prevalent view is that NPHPT is an early form of PHPT which may progress to frank hypercalcemia. Other hypotheses related to partial PTH resistance in bone and kidney or altered parathyroid sensing ( 23 , 24 ). In a recent study, it was supposed that NPHPT could be a different disease entity, probably more severe compared to mild asymptomatic primary hyperparathyroidism ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations